Doctors of osteopathic medicine (DO): a Canadian perspective - Evren, Sevan; Yuzhong Bi, Andrew; Talwar, Shuchi; Yeh, Andrew; Teitelbaum, Howard (Canadian Medical Education Journal, 2014)
Background: Doctors of osteopathic medicine (DO) are one of the fastest growing segments of health care professionals in the United States. Although Canada has taken significant leaps in the acknowledgment of US trained DOs, there continues to be a lack of understanding of the profession by Canadian trained physicians. In this article, we provide a brief overview of osteopathic medical education and training in the United States. Method: Current information of osteopathic training by American Association of Colleges of Osteopathic Medicine (AACOM) and American Osteopathic Association (AOA) was presented. Data pertaining to Canadians enrolled in osteopathic colleges was compared with allopathic (MD) and international medical graduates (IMGs). Results: Doctors of osteopathic medicine programs provide an additional pathway for students interested in pursuing a medical education. Canadian applications to osteopathic colleges are expected to grow due to successful post-graduate US residency matching, increased difficulty of matriculating at Canadian medical schools, and a greater awareness of the profession in Canada. Conclusions: Given the increasing enrollment of Canadian students in US osteopathic medical schools, we expect that Canadian DOs will play a significant role in shaping health care in both the US and Canada.